2016
DOI: 10.1080/15592294.2015.1136774
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromatin structure in mouse preimplantation embryos by fluorescent recovery after photobleaching

Abstract: Zygotes are totipotent cells that have the ability to differentiate into all cell types. It is believed that this ability is lost gradually and differentiation occurs along with the progression of preimplantation development. Here, we hypothesized that the loose chromatin structure is involved in the totipotency of one-cell stage embryos and that the change from loose to tight chromatin structure is associated with the loss of totipotency. To address this hypothesis, we investigated the mobility of eGFP-tagged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 43 publications
3
57
1
Order By: Relevance
“…Chromatin structure plays an important role in regulating transcription and it has been suggested that a loosened chromatin structure is involved in the promiscuous transcription that occurs during minor ZGA (5,25). We demonstrated by fluorescence recovery after photobleaching (FRAP) analysis that chromatin structure is extremely loosened in one-cell embryos and that it become tighter during the two-cell stage (26). FRAP analysis using an eGFP-tagged core histone estimates the mobility of core histones that reflects the looseness of chromatin structure (27,28).…”
Section: Significancementioning
confidence: 88%
See 3 more Smart Citations
“…Chromatin structure plays an important role in regulating transcription and it has been suggested that a loosened chromatin structure is involved in the promiscuous transcription that occurs during minor ZGA (5,25). We demonstrated by fluorescence recovery after photobleaching (FRAP) analysis that chromatin structure is extremely loosened in one-cell embryos and that it become tighter during the two-cell stage (26). FRAP analysis using an eGFP-tagged core histone estimates the mobility of core histones that reflects the looseness of chromatin structure (27,28).…”
Section: Significancementioning
confidence: 88%
“…1B), Pol I-mediated transcription would not be efficiently inhibited in our experimental conditions. Chromatin structure becomes "tighter" during MZT (26,39). The lack of a requirement for an enhancer-enhancers function by overcoming chromatin-mediated transcriptional repressionfor efficient expression of plasmid-borne reporter genes and promiscuous genome-wide transcription during minor ZGA likely reflect a loosened chromatin structure (5,25,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin structure is very relaxed after fertilization in both the mouse and human zygote (Wu et al 2018) and then slowly compacts throughout preimplantation development (Du et al 2017). The relaxed chromatin state is supported by the high mobility of histone proteins, which gradually decreases throughout preimplantation development, in line with the idea that increasing condensation of chromatin is associated with differentiation during development (Boskovic et al 2014;Ooga et al 2016).…”
Section: Global Chromatin Remodelingmentioning
confidence: 72%